ANALISIS KEUANGAN DAERAH PADA PEMERINTAH KABUPATEN TABALONG - YURIKA YURIKA; MUHAMMAD SALEH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims to examine and analyze the regional financial performance of the Tabalong District government based on regional financial analysis for the period og 2010 to 2017 the analysis techniques used include the Regional Financial Independence Ratio,Fiscal Decentralization Ratio,PAD Effectiveness Ratio,PAD Growth Ratio,and Activity Ratio. The data used are secondary data obtained from the Regional Finance Agency Of South Kalimantan Province and the Directorate General of Fiscal Balance of the Ministry of finance.             The results of the analysis obtained in this studi are : 1) Regional independence ratio in general from 2010 to 2017 falls into the very low category. 2) The Fiscal Decentralization Ratio in general from 2010 to 2017 falls into the very poor category 3) The PAD Effectiveness Ratio in general from 2010 to 2017 falls into the effective category 4) PAD Grow Ratio in general in 2010 to 2017 show that direct expenditure is greater than indirect expenditure in each of the fiscal years.Keywords : Regional Finance, regional autonomy